Benign Paroxysmal Positional Vertigo and Occult Subarachnoid Hemorrhage Complicated after Head Trauma - Qinghua Li; Shuangxing Hou; Hualan Yang (Case Reports in Medicine)
Benign paroxysmal positional vertigo (BPPV) is the most prevalent form of peripheral vertigo and is common in posttraumatic patients. Sometimes, posttraumatic BPPV and subarachnoid hemorrhage (SAH) exist together. How to effectively recognize SAH especially concealed bleeding before maneuver treatment for BPPV is worth paying attention by every clinician. Presently described is a case that when there are some clinical symptoms cannot be completely explained by simple BPPV, the combination of CT and FLAIR MRI sequences are needed in the early-stage detection of acute SAH.